FLASH CARD MEDIA UTILIZATION TO IMPROVE STUDENT ACTIVITY AND LEARNING OUTCOMES OF FAUNA DISTRIBUTION SUBTOPIC IN CLASS XI IPS I SMA XIN ZHONG SURABAYA - Felisia Ferra Ristanti; Fajar Arianto (Department of Geography Education, University of Jember, 2019)
The purpose of research to determine and describe whether the concept of flash card utilization is able to increase students activity students in learning in Geography subject. Though geography is a very important subject, particularly in determining the ample number of fauna found in Indonesia, which is even categorized as an endemic fauna. In addition, the manner in delivering subtopic which is considered monotonous by relying solely on reading books and summarizing what they have read are two things that are not surprising. Hence, those two facts encourage students not perform geography lessons enthusiastically. Considering the problems that occur, therefore I am interested in engaging the learning media